Handling Post Flight Documents PT XYZ Soekarno-Hatta International Airport: Human Error Analysis - Faturrahman, Mochamad Fikri; Prattiwi, Elisabeth Anna; Priyahapsara, Istyawan; Rahmawati, Fajar Khanif; Lukito, Indro (AIBPM Publisher, 2025)
PT XYZ organizes the storage of Post Flight Documents in accordance with the applicable SOP. Post Flight Documents are an important part of flight operations that have an influence on company performance and reputation. Errors in managing Post Flight Documents are mostly caused by human error such as input errors and errors in writing document labels. Data input errors can affect the FATA received by the flight crew. To deal with the occurrence of human error problems, the method that can be used is the Human Error Assessment and Reduction Technique (HEART) method, which is a technique for calculating the probability of human error. The type of research used in this research is descriptive. In this study there were 6 respondents. From the results of data collection and processing using the HEART method in the Post Flight Document handling process, it can be concluded that the activity that has the largest possible error value is in the data entry process into the system which has a HEP value of 4.7607966. Meanwhile, the smallest HEP is found in the task of numbering document packages and creating a receipt record which has a HEP value of 0.02912.